Proceedings of the 10th Economics &Amp; Finance Conference, Rome 2018
DOI: 10.20472/efc.2018.010.004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Female Top Manager in Innovation Activities: Case of Ceecs’ Firms

Abstract: The aim of this paper is to explore whether the gender of top manager plays an important role in innovation activities in selected CEE countries. For this purpose, a framework of logistic binary regressions is applied to the firm-level data from Business Environment and Enterprise Performance Survey (BEEPS). The research assesses the differences in firm innovation activities in CEECs considering the gender structure of the top management. Findings indicate that, on average, there is a lower possibility that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
0
0
1
Order By: Relevance
“…Reuvers et al [48] revealed a positive relationship between transformational leadership and innovative behavior, but employees report more innovative behavior when transformational leadership is displayed by male managers. Additionally, Becic and Vojinic [49] indicated that firms innovate more in terms of goods and services when they have a male leader. Females have been found to have a more democratic or participatory style, while men prefer a more autocratic or direct style [50].…”
Section: Leadership Style and Organizational Strategymentioning
confidence: 99%
“…Reuvers et al [48] revealed a positive relationship between transformational leadership and innovative behavior, but employees report more innovative behavior when transformational leadership is displayed by male managers. Additionally, Becic and Vojinic [49] indicated that firms innovate more in terms of goods and services when they have a male leader. Females have been found to have a more democratic or participatory style, while men prefer a more autocratic or direct style [50].…”
Section: Leadership Style and Organizational Strategymentioning
confidence: 99%
“…Buna paralel olarak ülkelerin kalkınmalarında kadın katılımının önemi Birleşmiş Milletler sürdürülebilir kalkınma hedeflerinde belirtilmiştir (Birleşmiş Milletler, 2019). Öte yandan firma üst yönetimlerinde kadın katılımının firma işleyişine farklı perspektifler getirdiği ve bundan doğan bilgi ve tecrübe çeşitliliğinin kalkınma ve inovasyonu canlandırdığı öne sürülmüştür (Barczak, Lassk ve Mulki, 2010;Ritter-Hayashi, Vermeulen ve Knoben, 2016;Becic ve Vojinic 2018). Ancak çoğu ülkede ve Türkiye'de kadınların üst yönetim pozisyonlarında bulunma düzeyleri son dönemlerde artmakla birlikte düşüktür (Smith vd., 2006;Örücü vd., 2007).…”
Section: Introductionunclassified